Estrutura populacional de Acetes paraguayensis Hansen, 1919 (Crustacea: Sergestidae) na foz do rio Tapajós, Baixo Amazonas, Pará, Brasil - Coelho, Yana Karine da Silva (2023)
The avium Acetes paraguayensis Hansen, 1919, is a small shrimp with great social and economic importance for families that make a living from fishing, however, research on this species is still scarce. In this study, some population structure parameters were estimated, such as biometrics, sex ratio, frequency distribution, abundance (in weight), weight-length relationship and the relative condition factor of the Acetes paraguayensis population captured at the mouth of the Tapajós River, Lower Amazonas, Santarém, Pará, Brazil allows obtaining important information that can contribute to management and future public policies. Captures were carried out with the aid of a trap called Matapí, from January to June 2023, every 15 days, at two pre-established points. 3,600 individuals were sampled, around 60% females (2,146) showing sexual dimorphism. The sex ratio was 0.68 males for each female. The distribution of cephalothorax length revealed that females are larger than males. Total abundance was 839.47 kg per trap. The weight-length relationship showed negative allometry decreasing as total length increases at a relatively higher rate than total weight. The relative condition factor showed the same behavior for males and females over time. In general, females stood out when compared to males, being larger in size, heavier and larger in quantity.